Mirada em Histórias de Alexandre, de Graciliano Ramos - Oliveira, Amanda de Andrade (2017)
The following study aims to analyze the literary work Histórias de Alexandre, written by Graciliano Ramos, by demonstrating that behind the fantasious universe that emerges from Alexandre’s narrative stories, being Alexandre a character-narrator, we measure the speech that concludes the entire novelist’s composition, in other words, through the dissimulation of a less mild reality, affected by a fabulous speech, we have contact with the miserable reality lived by the northeastern population which marks the novelist’s writing, whose ultimate goal is a search for narrative fidelity. The comic content present in the narrative is remarkable, being the hilarity an unusual trait in the compositions of the alagoano, we will seek to understand what finality it provides in the general understanding of the composition. In the composition, initially published at 1944, we met the character Alexandre, the former representative of the northeastern agrarian oligarchy who saw his riches collapse before the capitalist economic system. Due to his new socio economic condition, he creates a compensative reality to him and his companions. Should be noted, in this approach, the figure of a storyteller as a form of cultural preservation, mainly if we think that, according to Walter Benjamin’s lesson, “we are becoming increasingly poorer at communicable experience” (1987, p. 198).